Assessment of genetic variation and trait inter-relationship in landraces and elite cultivars of durum wheat (Triticum durum Desf.) - Kumar, Hitesh; Kumar, Mukul; Singh, Satyam; Singh, Dharm Veer; Gupta, Vikas; Singh, Shalesh Kumar (Journal of Cereal Research, 2024)
Eighteen landraces and elite cultivars of durum wheat were evaluated during Rabi 2020-21 to estimate genetic variability and trait inter-relationship for ten yield and yield contributing traits. Analysis of variance revealed the presence of significant variation among accessions for all measured traits. Correlation analysis indicated that fertile spikelet, grain number per spike, spike length and biological yield have a significant positive correlation with grain yield. Plant height, 100 seed weight and grains/spike appeared to be important traits based on their direct and indirect effect towards grain yield. Regression analysis revealed an adoptive regression coefficient for biological yield per plant while harvest index, spike length, total kernel weight, fertile spikelets, plant height, days to maturity, and 50% flowering revealed a regression coefficient which is non-adoptive. Local landraces performed well in comparison to elite cultivars in terms of yield per unit area. The estimated variations among genotypes in studied traits are due to genetic differences of genotypes and selection would be beneficial. Therefore, while exercising selection in wheat, characters like plant height, 100 seed weight and biological yield per plant must be given preference.